Serum adipsin levels in rheumatic diseases: defining its role in disease activity and progression in rheumatoid arthritis and axial spondyloarthritis - Novella-Navarro, Marta; González-Sánchez, Laura; Hernández-Breijo, Borja; Pérez De Diego, Rebeca; Sánchez-Corral, Pilar; López-Trascasa, Margarita; Miranda-Carús, Maria-Eugenia; Villalba, Alejandro; Balsa, Alejandro; De Miguel, Eugenio; Plasencia-Rodríguez, Chamaida; Corvillo, Fernando (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) and axial spondyloarthritis (axSpA) are the most common rheumatic diseases (RDs). They are characterised by chronic inflammation of the joints and musculoskeletal components. Adipose tissue releases adipokines that regulate numerous biological processes, including inflammation, thus stabilising the relationship between RDs and adipokines, such as adiponectin and leptin. The correlation between these adipokines and RA highlights a possible role of other adipokines in RDs. Therefore, we decided to analyse the role of the adipokine adipsin in the context of RDs. Adipsin levels were measured in serum from 233 patients (66 early-RA, 98 established-RA, and 69 axSpA) and 88 healthy controls (HCs). Associations between adipsin and clinical or demographic variables were assessed using univariate and multivariate regression models. The diagnostic utility of adipsin was evaluated using ROC curve analysis. Our study revealed that adipsin concentrations were significantly higher in both early-RA and established-RA patients than in axSpa and in HCs. No significant differences were found between axSpA and HCs. In early-RA, female sex and prednisone use were independently associated with higher adipsin levels. In established-RA, age and disease duration showed a positive association with adipsin concentrations. In axSpA, disease duration and CRP correlated with adipsin levels, but no consistent associations were observed for BMI or HLA-B27 status. ROC analysis revealed good discriminatory capacity of adipsin to differentiate early-RA from HCs (AUC = 0.82; optimal cut-off: 1.325 µg/mL). We provide evidence supporting the involvement of adipsin in the pathophysiology of RA and highlight its value as a new potential biomarker.